Adolescent Girls’ Awareness towards Reproductive Health in Baghdad City - mohammed, Shatha (Iraqi National Journal of Nursing Specialties, 2013)
Objective: is to determine the level of awareness concerning the reproductive health among adolescent girls in Baghdad City. Methodology: A cross sectional study was performed in order to assess the level of awareness regarding reproductive health among 180 adolescent school girls in the age 12-18 years from five secondary schools in Al-Seder Sector in Baghdad city, the data was collected by direct interview using constructed questionnaire to obtain socio-demographic characteristics and level of awareness related to reproductive health. The study started from September 2012 to January 2013. Results: the results show that the highest percentage of girls (47.7%) was in age (17-18) year’s age, (54.5%) at 4th class secondary school. The primary school is the educational background of their mothers (40.5%), (41.6%) of the respondents who have large family size. Television and internet were the first source of information (40.9%) of respondents. Good awareness regarding menstruation was recorded for (45.5%) of respondents, also good awareness regarding pubertal body changes among (51.1%) of respondents. Poor awareness recorded among respondents regarding both gynecological problems (45.6%) and (AIDS) (60.5%). Recommendations: the present study recommends that priority should be given to provide health education to increase the level of awareness regarding reproductive health for adolescent girls in Baghdad City especially that is related to gynecological problems and AIDS.